2019
DOI: 10.15295/bmij.v7i3.1229
|View full text |Cite
|
Sign up to set email alerts
|

Ki̇şi̇-Örgüt Uyumunun İşten Ayrilma Ni̇yeti̇ Üzeri̇ne Etki̇si̇nde İş Tatmi̇ni̇ Nasil Bi̇r Aracilik Rolü Üstleni̇r? Görgül Bi̇r Çalişma

Abstract: Bireylerin örgüt ile uyum derecesi, özellikleri, benimsediği tutumlar, roller, kişinin örgüt içerisinde iş tatminini düzeyini ve işten ayrılma niyetini belirlemektedir. Buna bağlı olarak kişinin işten ayrılma niyeti örgüt içerisinde belirli davranışları ve tutumları benimseyerek oluşmaktadır. Bu çalışmada, kişi örgüt uyumunun işten ayrılma niyeti üzerinde iş tatmininin nasıl bir aracılık rolüne sahip olduğu araştırılmaktadır. Veriler, Ankara’da ve Eskişehir’de faaliyet gösteren 14 farklı sektörde 303 kişiye an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 19 publications
1
2
0
Order By: Relevance
“…According to this finding, it can be said that employees with high person-organization fit also have high job satisfaction. Looking at the literature, the results reached in this study comply with the results of the studies conducted by Lim et al, (2019), Sökmen and Bıyık (2016), Karamanlıoğlu et al, (2019). Again, correlatively, it is seen that person-organization fit has a significant and positive effect on workplace happiness.…”
Section: Conclusion and Discussionsupporting
confidence: 90%
“…According to this finding, it can be said that employees with high person-organization fit also have high job satisfaction. Looking at the literature, the results reached in this study comply with the results of the studies conducted by Lim et al, (2019), Sökmen and Bıyık (2016), Karamanlıoğlu et al, (2019). Again, correlatively, it is seen that person-organization fit has a significant and positive effect on workplace happiness.…”
Section: Conclusion and Discussionsupporting
confidence: 90%
“…There is no research that examines these two variables in tourism enterprises in Turkey. Before this study, Karamanlıoğlu et al (2019) investigated the mediating role of job satisfaction in the effect of person-organization fit on intention to leave in 14 different sectors and found that person-organization fit had a negative effect on intention to leave. Considering these findings, the research question of our study was to investigate whether a similar effect could be seen in tourism enterprises and provided the basis for starting a study in this direction.…”
Section: Structured Abstractmentioning
confidence: 99%
“…And then in order to test whether person-organization fit has a significant effect on the employee's intention to leave, path analysis was conducted with structural equation model and the relevant hypothesis was tested. As a result of these analyzes, Karamanlıoğlu et al (2019) 's research findings covering 14 different sectors were compared with those in tourism enterprises. According to the findings, the following conclusions have been reached and suggestions for the managers have been presented:…”
Section: Conclusion and Suggestionsmentioning
confidence: 99%